2013
DOI: 10.1208/s12248-013-9503-5
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Applications of Metabolomics in Studying Chemopreventive Phytochemicals

Abstract: Abstract. Phytochemicals from diet and herbal medicines are under intensive investigation for their potential use as chemopreventive agents to block and suppress carcinogenesis. Chemical diversity of phytochemicals, together with complex metabolic interactions between phytochemicals and biological system, can overwhelm the capacity of traditional analytical platforms, and thus pose major challenges in studying chemopreventive phytochemicals. Recent progresses in metabolomics have transformed it to become a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 91 publications
0
13
0
1
Order By: Relevance
“…Data mining approaches to identify bioactive NPs in mixtures, from a library of terrestrial and marine organisms are currently being developed and will be essential for the development of effective multipleagent drugs from traditional medicines (Ngo et al 2013). Another aspect will be the assessment of the variation of the metabolome of body fluids in the framework of clinical trials, involving complex phytopharmaceutical or herbal preparations to completely assess the efficacy of such therapies though a systems Phytochem Rev (2015) 14:299-315 311 biology approach (van Wietmarschen et al 2009;Wang and Chen 2013).…”
Section: Future Directions In Natural Product Researchmentioning
confidence: 99%
“…Data mining approaches to identify bioactive NPs in mixtures, from a library of terrestrial and marine organisms are currently being developed and will be essential for the development of effective multipleagent drugs from traditional medicines (Ngo et al 2013). Another aspect will be the assessment of the variation of the metabolome of body fluids in the framework of clinical trials, involving complex phytopharmaceutical or herbal preparations to completely assess the efficacy of such therapies though a systems Phytochem Rev (2015) 14:299-315 311 biology approach (van Wietmarschen et al 2009;Wang and Chen 2013).…”
Section: Future Directions In Natural Product Researchmentioning
confidence: 99%
“…Such attention manifests in the public domain through the widespread use of dietary supplements that contain these chemicals [ 2 ] and in recommendations from public agencies to increase the consumption of fruits and vegetables because of the link between their consumption and cancer prevention [ 3 ]. In the scientific community, efforts to identify these chemicals from their multitude of sources and to evaluate their potential and underlying mechanisms to alter cell growth have been ongoing for several years [ 4 ]. A subset of phytochemicals, isoflavones, are polyphenolic compounds that resemble estrogen in their structure and biological effects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals modulate coding and non-coding RNA gene expression leading to the restoration of the normal signal transduction pathways [ 37 , 38 , 39 ]. Phytochemical intervention in chemotherapy are sustained by a higher number of clinical trials that have shown that these compounds increase the treatment efficiency and decrease the side effects, inducing apoptosis in cancer cells, reducing drug resistance and also the severity of comorbid conditions.…”
Section: Phytochemical Compounds and Cancermentioning
confidence: 99%